Introduction to the special issue on Balanced diets in food systems: emerging trends and challenges for human health and wellbeing - Descalzo, Adriana Maria; Muchenje, Voster; Mukumbo, Felicitas E.; Schönfeldt, Hettie C. (Elsevier, 2019)
Diets are constantly changing, creating new challenges to existing food systems to deliver the food to meet these requirements. With a new focus on the outcomes of food systems in terms of human health and well-being, the question arises: what are the emerging trends and challenges that are critical to be considered in order to meet these needs. Dietary consumption patterns differ significantly amongst consumers from different regions of the world as well as between societies amongst people with different socio-demographic backgrounds. However for several decades, the amount of energy in the food supply has increased, and inexpensive, processed, energy dense foods have become widely marketed and available